Competition and the density dependence of metabolic rates. (8th April 2013) - DeLong, John P.; Hanley, Torrance C.; Vasseur, David A.; Humphries, Murray
Summary Although mass and temperature are strong predictors of metabolic rates, there is considerable unexplained variation in metabolic rates both within and across species after body size and temperature are taken into account. Some of this variation may be due to changes in the rate of food intake with population density, as metabolism depends on the throughput of food to fuel biochemical reactions. Using data collected from the literature, we show that individual metabolic rates are negatively correlated with population density for a wide range of organisms including primary producers and consumers. Using new data for the zooplankter Daphnia ambigua, we also find genotypic variation in the relationship between metabolic rate and population density. The relationship between metabolic rate and population density generally follows a power law scaling, and within a population, density‐correlated variation in metabolism can span two orders of magnitude. We suggest that density‐dependent metabolic rates arise via competitive effects on foraging rates (both exploitation and interference competition), combined with an activity response to accommodate the resource constraint induced by competition. Standard ecological models predict the kind of density‐dependent foraging patterns that could give rise to density‐dependent metabolic rates, but this has generally not been investigated. Our results indicate that after body mass and temperature, population density represents an important third axis that may account for a large amount of unexplained variance in metabolic rates within and among species. The effect of population density on metabolism has implications for the scaling of metabolic rates from individuals to populations and the relative performance of species and genotypes and therefore also for community assembly and evolution.